The disciple is the salt and the light of the world: Người môn đệ là muối và ánh sáng của thế giới - Dương Hải Văn (Khoa Học Công Giáo và Đời Sống, 2022)
The text defines the nature and mission of a disciple of Jesus. In it, the disciple is likened to salt to make life saltier and a light to shine into the darkness of this world. When he understands his role and responsibility, the disciple will be more confident in his life of faith and his life of witness to everyone. From there, the mission entrusted by Jesus will be powerfully realized in the life of Christians in this day and age.